2017
DOI: 10.1080/03670244.2017.1327855
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Consumption Frequency and Its Relationships to Overall Diet Quality, Using Healthy Eating Index 2010, and Body Mass Index among Adolescents in a Low-Income Urban Setting

Abstract: The aim of this study was to describe the relationship of breakfast frequency to diet quality and BMI among low-income, predominantly African American adolescents aged 9–15 (n = 239). Mean frequency of breakfast consumption was 5.0 ± 0.15 times per week. A significant, positive relationship was seen between HEI scores and frequency of breakfast consumption (p = .01). Dairy (p = .02) and whole grains (p < .01) HEI component scores were significantly related to breakfast frequency. No relationship was seen betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…These findings were confirmed in longitudinal studies that indicated a direct association between irregular breakfast consumption and increased BMI Z-score among African [34] and Finnish [9] adolescents. However, a study involving low-income African-American adolescents did not find an association between irregular breakfast habits and BMI [35].…”
Section: Discussionmentioning
confidence: 86%
“…These findings were confirmed in longitudinal studies that indicated a direct association between irregular breakfast consumption and increased BMI Z-score among African [34] and Finnish [9] adolescents. However, a study involving low-income African-American adolescents did not find an association between irregular breakfast habits and BMI [35].…”
Section: Discussionmentioning
confidence: 86%
“…The present analyses of 2011-2014 NHANES data asked: what breakfast patterns were associated with highest quality diets for children and adults [1,4,6,19,36]. The answer could shape future dietary guidelines that are increasingly concerned with foods and food groups as well as with nutrients of concern.…”
Section: Discussionmentioning
confidence: 95%
“…Breakfasts that provide more nutrients than calories can be viewed as nutrient-rich meals [1][2][3][4]. Eating breakfast has been associated with higher-quality diets and with higher intakes of key nutrients and desirable food groups [5,6]. By contrast, skipping breakfast has been linked to lowerquality diets, lower cognitive performance, and a host of negative health outcomes [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…“Yes/No” questions were used to determine whether breakfast skipping had occurred on the day of the survey. Although inconsistencies inherent in assessing breakfast skipping are clearly evident in the literature, doing so on the basis of a single day, ie, the day of the survey or the previous day, is common practice in the literature (Hopkins et al, ; Mullan et al, ; Pedersen, Holstein, Laursen, & Rasmussen, ). Pedersen et al () postulate that a 1‐day recall measurement of breakfast consumption reflects a pattern of consumption among adolescents, as there is good agreement between single‐day and multiple‐day recalls ( Pedersen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Research findings indicate that a higher frequency of breakfast consumption is related to lower systolic blood pressure, body mass index, body fat, dyslipidemia, insulin resistance, and metabolic syndrome (Cayres, Júnior, Barbosa, Christofaro, & Fernandes, ; Marlatt, Farbakhsh, Dengel, & Lytle, ). A positive relationship has also been found between regular breakfast intake and overall nutritional health and diet quality (Hopkins, Sattler, Steeves, Jones‐Smith, & Gittelsohn, ).…”
Section: Introductionmentioning
confidence: 97%